Towards understanding interactions between Sustainable Development Goals: the role of environment–human linkages - Scharlemann, Jörn P. W.; Brock, Rebecca C.; Balfour, Nicholas; Brown, Claire; Burgess, Neil D.; Guth, Miriam K.; Ingram, Daniel J.; Lane, Richard; Martin, Juliette G. C.; Wicander, Sylvia; Kapos, Valerie (Sustainability science, 2020)
Only 10 years remain to achieve all Sustainable Development Goals (SDGs) globally, so there is a growing need to increase the effectiveness and efficiency of action by targeting multiple SDGs. The SDGs were conceived as an ‘indivisible whole’, but interactions between SDGs need to be better understood. Several previous assessments have begun to explore interactions including synergies and possible conflicts between the SDGs, and differ widely in their conclusions. Although some highlight the role of the more environmentally-focused SDGs in underpinning sustainable development, none specifically focuses on environment–human linkages. Assessing interactions between SDGs, and the influence of environment on them can make an important contribution to informing decisions in 2020 and beyond. Here, we review previous assessments of interactions among SDGs, apply an influence matrix to assess pairwise interactions between all SDGs, and show how viewing these from the perspective of environment–human linkages can influence the outcome. Environment, and environment–human linkages, influence most interactions between SDGs. Our action-focused assessment enables decision makers to focus environmental management to have the greatest impacts and to identify opportunities to build on synergies and reduce trade-offs between particular SDGs. It may enable sectoral decision makers to seek support from environment managers for achieving their goals. We explore cross-cutting issues and the relevance and potential application of our approach in supporting decision making for progress to achieve the SDGs.